INNOVATIONS IN CORPORATE SOCIAL RESPONSIBILITY MANAGEMENT: CHALLENGES AND PROSPECTS FOR MODERN BUSINESS - ZERKAL, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores innovative approaches to corporate social responsibility (CSR) management in the context of digital transformation. The relevance of the study is determined by the growing role of CSR in ensuring sustainable business development and the increasing expectations of stakeholders regarding corporate transparency, accountability, and ethical conduct. The purpose of the research is to analyze the impact of digital technologies on CSR efficiency and to identify challenges and prospects for their implementation in corporate governance.The research methodology includes a systematic approach to studying CSR management practices, comparative analysis of traditional and digitalized CSR models, and evaluation of technological tools such as Big Data, artificial intelligence, blockchain, and the Internet of Things. The study also applies analytical methods to assess the effectiveness of digital solutions in monitoring and reporting corporate social and environmental initiatives.The findings indicate that the integration of digital technologies into CSR enhances corporate accountability, optimizes reporting processes, and facilitates proactive engagement with stakeholders. Digitalization allows for real-time tracking of environmental and social indicators, automation of sustainability reporting, and more precise measurement of CSR outcomes. However, the research highlights significant challenges, including the lack of standardized evaluation methods, the complexity of data integration, and the necessity of adapting business strategies to new digital tools. Addressing these challenges requires companies to develop cross-sector partnerships and implement comprehensive digital transformation strategies.The practical significance of the article lies in its contribution to the development of innovative CSR management practices by demonstrating how digital solutions can improve the efficiency and transparency of corporate social responsibility efforts. The results provide insights for business leaders, policymakers, and researchers interested in enhancing CSR through technology-driven approaches. The study underscores the need for further investigation into the long-term impact of digital transformation on corporate sustainability and the development of unified assessment methodologies for CSR initiatives.
Keywords: Corporate Social Responsibility (CSR); innovation; management; digital business transformation; Big Data; artificial intelligence (AI); automation; stakeholders; sustainable development; business; modern technologies